THE INFLUENCE OF FERTILIZERS ON THE CHEMICAL COMPOSITION AND CONCENTRATION OF SOIL SOLUTION IN IRRIGATED SOILS - Ermatova Munojat; Sidikov Saidjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Seasonal changes in the chemical composition and concentration of the soil solution of irrigated automorphic soils in different agricultural zones were studied. It is established that the composition of soil solutions, concentrations and ratios of various compounds in it are subject to seasonal variation during the growing season. This is facilitated by the process of plant nutrition. At the beginning of the growing season, there is a high concentration of soil solution, and at the end of the growing season, a low concentration.